The incidence of teaching for understanding methodology on the reading skill development for students attending the third level of the ESPE onsite English program during the October 2007 march 2008 term - Hidalgo Salazar, Francisco Enrique (2009)
To do this research, I have been followed a scheme proposed by the Army Polytechnic School Language Department which clearly specifies step by step each detail of how to develop a research and obtain the requirement results which permit me to complete it successfully, without forgetting the unconditional support of my dear tutors. First of all, I selected the subject to be investigated which was not difficult for me, as student, I have had experiences in the English teaching-learning process during my studies at school, besides I have practiced at the Department of Languages as a fulfillment of the requirement to obtain the Bachelors´ Degree in Applied Linguistics. I found some negative aspects in the development of English classes which give me a trace to start the first step of my research. Through observation and suggestion of some colleagues and specialists, it was possible to select this interesting subject which would affect the student s life. The main subject is The incidence of Teaching for Understanding (TFU) Methodology on the reading skill development. Immediately I started to find out the primary and secondary sources which permitted me to understand this subject much better and have good arguments to do the theoretical framework in which I support my research. This subject was chosen; because the Teaching for Understanding methodology is one of the most important projects in the teaching-learning process around the world, I have observed the lack of interest in reading the English language in the Department of Languages. This produces negative consequences and does not permit to develop this important skill in an excellent way. Through this research I would like to help teachers to see the importance in teaching this methodology on reading, during their daily activities